Modelling dispersion of smoke from wildfires in a Mediterranean area. (1st December 2014) - Cesari, Rita; D'Isidoro, Massimo; Maurizi, Alberto; Mircea, Mihaela; Monti, Francesca; Pizzigalli, Claudia; Tampieri, Francesco
We present a modelling system for the estimation of forest fire emissions ( prebolchem-fire ) and their inclusion in the atmospheric composition model BOLCHEM. Emission fluxes have been estimated following the methodology proposed by Seiler and Crutzen (1980) and using MODIS 'burned area product'. Then they are modulated following the WRAP approach (WRAP, 2005). This approach is also used for the estimations of fire emission height. Model simulations have been performed for the period 22–30 August 2007, in which fires were most severe in Greece, Albania and Algeria. The estimated emission fluxes have been compared with those estimated by the global model FINNv1 (fire inventory from NCAR) and the difference between the two emissions have been discussed. The modelled concentration of black carbon aerosol is compared with measurements at PEARL station lidar, Tito Scalo, Potenza (40.63°N, 15.80°E, 760 m asl), Italy, on 30 August 2007. We discuss the discrepancies between the measured and modelled vertical distribution concentrations of black carbon aerosol, probably due to uncertainties related to the estimation of the total flux and of the injection height of the smoke.